Analisis Determinan Pengungkapan Corporate Social Responsibility: Studi pada Perusahaan Indeks LQ45 - Dwitarini, Ni Made; Ratna Sari, Maria Mediatrix (E-Jurnal Akuntansi, 2021)
Companies should pay attention to Corporate Social Responsibility (CSR). Public companies are required to prepare a sustainability report, but the disclosure is voluntary, which causes the aspects that are reported by each company to be different. This difference is thought to be caused by several factors. The research objective is to examine the factors that are thought to affect CSR disclosure. The factors in question are profitability, leverage, company size, and corporate governance mechanisms proxied by board of commissioners, independent board of commissioners, and audit committee. Tests were carried out on the LQ45 index company during the 2018-2019 period. The sample was selected by purposive sampling technique. Data collection using document study method, and analyzed using multiple linear regression analysis. The results of the analysis show that board of commissioners has a negative effect and audit committee has a positive effect on CSR disclosure. Meanwhile, the other four causes tested had no effect. Keywords: Profitability; Leverage; Company Size; Disclosure of Corporate Social Responsibility.